(untitled) (Marketing Journal, 2025)
This article analyzes the prospects of implementing digital transformation and Big Data technologies in Uzbekistanʼs meteorological service. It briefly reviews the history and development stages of meteorology and highlights the importance of modern meteorological services. The article discusses the capabilities of collecting, processing, and analyzing meteorological data in real-time using digital technologies and artificial intelligence. Special emphasis is placed on the role of Big Data technologies in improving weather forecast accuracy, timely detection of emergencies, and monitoring climate change. The article stresses the need to modernize Uzbekistanʼs meteorological service and adopt digital solutions to enhance the quality of meteorological information in socio -economic sectors.